Enhancing Agribusiness Ecosystems for Rural Economic Growth: Insights from Papua, Indonesia - Pusvita, Ema; Hermawati, Lisa; Lastinawati, Endang; Rosmawati, Henny (Jurnal AGRISEP, 2026)
The formation of a strong agribusiness ecosystem was a key driver of sustainable economic development in rural areas. This paper aims to examine the factors that support opportunities for strengthening the agribusiness ecosystem and its impact on rural economic performance. This paper used a survey to obtain responses from 200 respondents in various underdeveloped areas in Papua. Statistical evaluation of the collected data used PLS-SEM. The results showed that the correlations of all tested relationships were statistically significant (p < 0.05). Institutional support had a positive and significant effect on the agribusiness ecosystem (β = 0.312, t = 4.865, p = 0.000) and economic impact (β = 0.215, t = 3.457, p = 0.001). Market access also significantly influences the agribusiness ecosystem (β = 0.287, t = 4.236, p = 0.000) and economic impact (β = 0.198, t = 3.015, p = 0.003). Similarly, human resource quality shows a positive influence on the agribusiness ecosystem (β = 0.225, t = 3.278, p = 0.001) and economic impact (β = 0.176, t = 2.865, p = 0.004). Technology access significantly strengthens the agribusiness ecosystem (β = 0.298, t = 4.574, p = 0.000) and improves economic outcomes (β = 0.203, t = 3.186, p = 0.002). In addition, the agribusiness ecosystem itself has a significant and very high influence on economic outcomes (β = 0.352, β = 5.012, β = 0.000). The agribusiness ecosystem moderates the impact of institutional, technological, market, and human factors on economic performance.